2015
DOI: 10.1097/hjh.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

BK channel β1-subunit deficiency exacerbates vascular fibrosis and remodelling but does not promote hypertension in high-fat fed obesity in mice

Abstract: Objective Reduced expression or increased degradation of BK (large conductance Ca2+-activated K+) channel β1-subunits has been associated with increased vascular tone and hypertension in some metabolic diseases. The contribution of BK channel function to control of blood pressure (BP), heart rate (HR) and vascular function/structure was determined in wild-type and BK channel β1-subunit knockout mice fed a high-fat or control diet. Methods and Results After 24 weeks of high-fat diet, wild-type and BK β1-knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(102 reference statements)
2
17
1
Order By: Relevance
“…Studies with knockout mice showed that the presence of the β1 subunit was critical to normal BK channel function in vascular smooth muscle cells (Werner et al, 2007, 2008). One recent report showed that β1 deficiency exacerbated vascular fibrosis and remodeling (Xu et al, 2015). The knockout mice of β4 subunit showed signs of an epileptic phenotype (Brenner et al, 2005), and the β2 knockout mice had an increased tendency toward spontaneous burst firing in the adrenal medullary chromaffin cells (Martinez-Espinosa et al, 2014).…”
Section: Physiological and Pathological Relevance Or Rolesmentioning
confidence: 99%
“…Studies with knockout mice showed that the presence of the β1 subunit was critical to normal BK channel function in vascular smooth muscle cells (Werner et al, 2007, 2008). One recent report showed that β1 deficiency exacerbated vascular fibrosis and remodeling (Xu et al, 2015). The knockout mice of β4 subunit showed signs of an epileptic phenotype (Brenner et al, 2005), and the β2 knockout mice had an increased tendency toward spontaneous burst firing in the adrenal medullary chromaffin cells (Martinez-Espinosa et al, 2014).…”
Section: Physiological and Pathological Relevance Or Rolesmentioning
confidence: 99%
“…Male adult mice (19.1±0.8 weeks old) were used for the duration of this experiment. The db/db mouse was selected because it produces a reliable hypertensive response and to avoid the confounding effects of weight loss associated with the impact of myostatin in diet‐induced obesity models 19, 20, 21, 22, 23, 24. To generate animals for this study, myostatin knockout mice were crossed onto the db/db background, as previously described 25.…”
Section: Methodsmentioning
confidence: 99%
“… showed that higher ratio of β1 subunit: α‐subunit in cerebral VSMCs related to that in skeletal muscle may lead to higher Ca +2 sensitivity of BK Ca current in cerebral arteries. It is well known that BK Ca is primarily activated either by an elevation of the [Ca +2 ]i or by membrane depolarization and maintain MP and vascular myogenic tone through negative feedback modulation . Hence, BK Ca affects as a relaxing negative feedback mechanism after agonist‐induced membrane depolarization and extracellular Ca +2 entry in most isolated arteries obtained from animals and humans .…”
Section: Basic Properties Of Potassium Channelsmentioning
confidence: 99%
“…Impaired β1 subunits inhibited BK Ca activation in cerebral arteries of hypertensive rats, leading to dysfunctional vasodilation . Disruption and knockout of the BK Ca ‐β1 gene ( KCNMB1 ) were associated with elevated blood pressure in mice, and downregulation of the β1 subunit was been reported in hypertensive rats . β1 knockout mice were hypertensive, indicating that uncoupling BK Ca from RyRs by the loss of the β1 subunit alone is sufficient to induce hypertension .…”
Section: Pathophysiological Roles Of Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation